2021
DOI: 10.1108/jstp-11-2020-0251
|View full text |Cite
|
Sign up to set email alerts
|

Co-creating dementia care: manoeuvring fractured reflexivity in service design

Abstract: PurposeThis study aims to theorise and empirically investigate how vulnerable users suffering from cognitive impairments can be involved in service design.Design/methodology/approachThe data were collected through an ongoing field study following the processes of designing new forms of dementia care. The data consist of document studies, observations and interviews with actors involved in the service design process.FindingsThe findings demonstrate how the involvement of vulnerable users with cognitive impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Gender norms are a psychosocial source of customer vulnerability (Baker et al , 2005; Baker and Mason, 2012) and consist of perceptions including stigma, identity and status-loss. As Table 1 outlines, previous empirical TSR research examining customer/consumer vulnerability has identified the importance of these psychosocial sources of customer vulnerability as both ex ante (McGraw et al , 2020; Tanner et al , 2020) and ex post (Bast et al , 2021; Mele et al , 2022; Raciti et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender norms are a psychosocial source of customer vulnerability (Baker et al , 2005; Baker and Mason, 2012) and consist of perceptions including stigma, identity and status-loss. As Table 1 outlines, previous empirical TSR research examining customer/consumer vulnerability has identified the importance of these psychosocial sources of customer vulnerability as both ex ante (McGraw et al , 2020; Tanner et al , 2020) and ex post (Bast et al , 2021; Mele et al , 2022; Raciti et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, customer/consumer vulnerability literature is dominated by cross-sectional research with limited examination over time, particularly timeframes spanning several years. The longitudinal research already undertaken specific to transformative services is mostly between six and 13 months (Amine and Gatfaoui, 2019; Batat, 2015; Mende and Van Doorn, 2015), with the exception of some 2–2.5 year studies (Bast et al , 2021; Boenigk et al , 2021). Longitudinal research with relatively short timeframes does not capture progressive phenomena particular to complex health services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ensuring users, especially vulnerable users, and those with constrained capacity, can claim their right to participation and feel empowered to directly voice their needs requires an Designing energy solutions exploration of diverse methods for involvement (Bast et al, 2021). A range of participatory design methods may be used in the creation of new and innovative services including design thinking (Brown, 2008;Brown and Wyatt, 2010) and co-design (Trischler et al, 2019;Schmidtke et al, 2021).…”
Section: A Participatory Design Approachmentioning
confidence: 99%
“…Ensuring users, especially vulnerable users, and those with constrained capacity, can claim their right to participation and feel empowered to directly voice their needs requires an exploration of diverse methods for involvement (Bast et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These constraints have been linked to a lack of skills and competencies, language barriers, physical health conditions, cognitive impairments and other associated factors (Davey and Grönroos, 2019; Dietrich et al , 2017; Mulvale et al , 2019). Hence, including the voices of consumers in the design and transformation of services, specifically by targeting vulnerable groups, depends on the ability to involve representations and representatives that effectively convey the needs and perspectives of service users (Bast et al , 2021; Eriksson, 2019; Røhnebæk and Bjerck, 2021). The use of representatives can be seen as a way of working around, or coping with, the diverse constraints that limit the direct involvement of vulnerable groups.…”
Section: Introductionmentioning
confidence: 99%